Evaluation of the Effects of Bromelain and Papain Enzymes on Shear Bond Strength of Composite Resin to Enamel - Farahnaz Sharafeddin; Mohammad Hossein Yazdanpanah; Zahra Jowkar (International Journal of Dentistry)
Aim. This study aimed to evaluate the effects of 6% bromelain and 10% papain enzymes on shear bond strength (SBS) of composite resin to enamel compared to conventional 37% phosphoric acid etching. Materials and Methods. 50 human maxillary premolar teeth were randomly divided into 5 groups (G1–G5/n = 10). In G1 and G2, after etching enamel with 37% phosphoric acid for 15 seconds and washing the surface, 10% papain and 6% bromelain enzymes were used, respectively. In G3 and G4, 6% bromelain or 10% papain enzymes were applied on enamel. In G5, the enamel surface was etched with 37% phosphoric acid for 15 seconds. A two-step etch-and-rinse adhesive system (Adper Single Bond 2) was applied. A nanohybrid composite (Z350) was placed using Teflon molds. All the samples were then subjected to the SBS test using a universal testing machine. Data analysis was performed using a one-way ANOVA test followed by the Tukey test. p values less than 0.05 were considered significant. Results. Comparison of the mean SBS between G1, G2, and G5 shows no significant differences (p>0.05); however, they had higher mean SBS compared with G3 and G4 (p<0.0001). Conclusions. The shear bond strength of composite to enamel was not affected significantly using either 6% bromelain or 10% papain enzymes after 37% phosphoric acid application. Moreover, 6% bromelain and 10% papain enzymes were not as effective as 37% phosphoric acid alone.